Shape changes, exocytosis, and cytosolic free calcium changes in stimulated human eosinophils. - Kernen, P (1991)
Essentially pure preparations of normal density eosinophils obtained from patients with hypereosinophilic syndrome (HES) were stimulated with complement factor 5a (C5a), platelet-activating factor (PAF), FMLP and neutrophil-activating peptide (NAP-1/IL-8). Three responses were studied, the transient rise in cytosolic free calcium concentration ([Ca2+]i) (derived from indo-1 fluorescence), shape changes (measured by laser turbidimetry), and exocytosis of eosinophil peroxidase (EPO) (assessed by H2O2/luminol-dependent chemiluminescence). Responses were obtained with all four agonists, but C5a and PAF were by far more potent than FMLP and NAP-1/IL-8, which induced only minor effects. Pretreatment of the cells with pertussis toxin attenuated [Ca2+]i changes, EPO release and, to a lesser extent, shape changes, indicating that GTP-binding proteins of Gi-type are involved in receptor-dependent signal transduction processes leading to these responses. A clear dissociation was observed in the control of the shape change response and EPO exocytosis. The shape change was not affected by Ca2+ depletion or treatment with the protein kinase inhibitor staurosporine, but exocytosis was prevented by Ca2+ depletion and markedly enhanced by staurosporine. The activation of the contractile system, leading to shape changes and motility, thus appears to be independent of the classical signal transduction pathway involving phospholipase C, a [Ca2+]i rise and protein kinase C activation. Exocytosis is, as expected, Ca2+ dependent and appears to be under a negative control involving protein phosphorylations.